Digesting design: Le Corbusier’s Immeuble-villas food strategy - Rodríguez-Lora, J.-A.; Sequeira, M. (Eating, building, dwelling: About food, architecture and cities, 2025)
Presented for the first time at the 1922 Paris Salon d’Automne, the Immeuble-villas was conceived by Le Corbusier as a new typology of collective housing in which spaces for private and communal use were mixed. In order to deal with the various crises surrounding habitation -housing, domestic service, cost of living- Le Corbusier gave an essential role to the management of food within the building. He advocated the joint purchase of products directly from the provinces at wholesale prices, seeking savings of around 40% – compared to buying through the large grocery traders. For food preparation, although each flat would have a private kitchen, each building would contain a common kitchen staffed by qualified personnel, ready to serve food at any time. A search in the archives of the Fondation Le Corbusier has unearthed a set of documents that allow us to retrace the different phases of the food process: purchase, supply, preparation and service of the food. According to Le Corbusier, actions would feed the inhabitants of this disturbing building, which was never built but which even at the time sought to answer many of the questions that today, one hundred years later, we are still asking ourselves.